2022
DOI: 10.3390/molecules27154672
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of Broccoli By-Products: Technological, Sensory and Flavour Properties of Durum Pasta Fortified with Broccoli Leaf Powder

Abstract: The aim of this study was to evaluate the effect of broccoli leaf powder (BLP) incorporation on the technological properties, sensory quality and volatile organic compounds (VOCs) of durum wheat pasta. Incorporation of BLP increased cooking loss; however, all pasta samples were found to be in the acceptable range of 8 g/100 g. The addition of BLP decreased optimal cooking time and water absorption but increased the swelling index. Firmness and total shearing force decreased with increased BLP content. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…At the same time a simultaneous double reduction in SFA in total fatty acids was obtained, which clearly resulted in the higher nutritional value of the produced snack pellets (Table 4). Drabińska et al [62] also observed that the addition of broccoli leaf powder to the pasta also resulted in a significant increase in fat content. In general, broccoli is considered a low-fat product.…”
Section: Fatty Acid Profilesmentioning
confidence: 94%
See 1 more Smart Citation
“…At the same time a simultaneous double reduction in SFA in total fatty acids was obtained, which clearly resulted in the higher nutritional value of the produced snack pellets (Table 4). Drabińska et al [62] also observed that the addition of broccoli leaf powder to the pasta also resulted in a significant increase in fat content. In general, broccoli is considered a low-fat product.…”
Section: Fatty Acid Profilesmentioning
confidence: 94%
“…Interestingly and importantly, although the extrusion process may reduce the content of bioactive compounds, the same process may increase their bioavailability, which at the same time leads to an increase in the actual volume of absorbed bioactive compounds [61]. Of note, Drabińska et al [62] tested the usability of broccoli by-products in durum pasta fortified with 2.5 and 5% of broccoli leaf powder. They also found an increase in ash and protein and also fat content, with slight decrease of carbohydrates content.…”
Section: Proximate Chemical Compositionmentioning
confidence: 99%
“…Drabińska et al (2018) investigated the effects of adding broccoli leaf powder to gluten-free sponge cakes and found that by adding 2.5% broccoli leaf powder to replace starch has increased the antioxidant activity of the new gluten-free sponge cakes. Drabińska et al (2022) found that the optimal cooking time and water absorption were observed to be shortened when 5% broccoli leaf powder was added to durum wheat pasta, which might boost the mineral and protein contents of the pasta without altering the sensory evaluation.…”
Section: Preparation Of Leaf Protein Powdermentioning
confidence: 99%
“…Its low cost and versatility in incorporating ingredients of various types, such as legumes, vegetables, cereals, and fish powder 1 make it an excellent vehicle for both bioactive molecules and new flavors. 2 The partial and/or total replacement of semolina is a challenge for the pasta industry, as variations in traditional formulations, both dry and fresh versions, should not adversely affect the organoleptic properties and technological quality. 3 Among the candidates for supplementation with semolina, barley flour has attracted the attention of researchers for its high nutritional value.…”
Section: Introductionmentioning
confidence: 99%